Relationship between dietary habits and cardiovascular disease risk factors among commercial drivers in northeast Nigeria - Emmanuel, Bidemi Bernice; Onuoha, Nnenna Ola (The North African Journal of Food and Nutrition Research, 2024)
Background: Unhealthy dietary practices are prevalent among commercial drivers, and poor diet quality is well known to predispose individuals to cardiovascular diseases (CVDs).Aims: This study investigated the relationship between dietary habits and cardiovascular disease risk factors among commercial drivers in northeast Nigeria.Subjects and Methods: This descriptive cross-sectional study was conducted in northeast Nigeria, involving 924 commercial drivers selected using a multistage sampling technique. Dietary habits were assessed using a pretested structured Food Frequency Questionnaire adapted from the WHO STEPS survey. Statistical analysis was performed using SPSS software.Results: Only 16.3% and 8.1% of participants consumed fruits and vegetables daily, with over half failing to meet the recommended daily servings. The majority (82.1%) ate meals during trips, and 56.4% consumed breakfast outside the home. Consumption of carbonated drinks and snacks was reported by 15.2% of drivers. A significant positive correlation (p < 0.05) was observed between the frequency of meals consumed during trips (r = 0.067) and body mass index.  A significant negative correlation (p < 0.01) existed between eating during trips (r = -0.134) and blood pressure. Additionally, a significant positive correlation (p < 0.05) was found between the consumption of carbonated drinks and snacks (r = 0.183) and low-density lipoprotein (LDL), as well as between vegetable servings (r = 0.149) and triglyceride levels.Conclusions: The low intake of fruits and vegetables and the high reliance on food consumed outside the home among commercial drivers may increase their risk of cardiovascular diseases. Targeted nutrition education is necessary to promote healthier dietary habits among this population.
Keywords: Dietary habits; Association; Commercial drivers; Hypertension; Diabetes mellitus; Lipid profile; Cardiovascular disease risk factors